The Art and Science of Decision-Making : Mastering Critical Thinking and Problem-Solving for Enhanced Productivity and Success - Phillips, Annette ([publisher not identified], 2023)
Discover how to master decisions in any part of your life with step-by-step techniques and proven tools. Do you suffer from analysis paralysis and decision fatigue? Is your risk appetite as low as the freezing temperatures on a winter's morning? How often do you experience indecision when considering work, school, or home options? Have you lost count of the missed opportunities caused by fear of failure or regret? If so, you aren't alone. Indecision has become a pandemic. In fact, recent research proves that 20% of adults are indecisive. But the good news? You can stop feeling like a deer in headlights when faced with choices! Instead, embrace the new decision-making framework. Say goodbye to FOMO, analysis paralysis, decision fatigue, or a crippling risk appetite that leads nowhere.